Relação de equivalência, conjunto quociente e aplicações - Frota, Marcelo Briseno (2017)
This work initially aims at presenting the construction of integers, rational and real, as well as their equivalence relations. We will also analyze the equivalence classes in a quotient space, the theorem of the nucleus and the image, form of Jordan and finalizing with the study of surfaces quotients: projective plane, torus and bottle of Klein.